An Assessment of the Ethnobotanical Knowledge of Danuwar Community in Udayapur District, Nepal - Sharma, Prakriti; Bhattarai, Shreehari (Journal of Plant Resources, 2025)
This study investigated the Danuwar community’s traditional plant-based knowledge dwelling in the Katari municipality, Udayapur district, with the objective of documenting the diversity, medicinal applications, and cultural significance of the plant species they utilize. Data was collected from March to June, 2024 using semi-structured questionnaires, field observations, and group discussions with 89 informants (43 men and 46 women), along with 6 key informant interviews and 2 focus group discussions. Data was analyzed in R studio using Ethnobotanical indices: Use value (UV), Use Reports (UR), Relative Frequency of Citation (RFC) and Cultural Value (CV). A total of 111 plant species from 103 genera and 58 families were documented, primarily for medicinal, cultural, and daily use, with herbs being the most commonly used and 24% of documented species were used to treat gastro-intestinal/digestive disorders. The most significant species was Achyranthes aspera (RFC 0.568) whereas Aegle marmelos had the highest use value (UV 0.784) with 69 use reports. Similarly, Achyranthes aspera shows culturally significant, with their highest Cultural Value (CV 0.100). Deforestation, encroachment, grazing, forest fire and unsustainable practices threatened the use of these valuable plants. Raising awareness about the importance of non-timber forest products and empowering the Danuwar community can help to preserve their cultural heritage and medicinal practices for future generations.